First fine mapping of a strain of Rhizoctonia Solani AG-3, causing tobacco target spot - Pan Ma; Mengjuan Qiu; Rubing Xu; Zhao Wang; Tom Hsiang; Junbin Huang; Lu Zheng; Yanyan Li (BMC Genomic Data)
Abstract Objectives Rhizoctonia solani AG-3 is the casual pathogen of tobacco target spot, a serious fungal disease of tobacco that severely decreases yield and quality. To examine the pathogenic mechanisms of this fungus, it is crucial to understand its genetics. The objective of this work was to generate the first fine mapping of a R. solani AG-3 strain from tobacco and to explore potential virulence genes, which will lay the foundation for genetic characterization and its interaction with tobacco. The functional genes involved in this study can be used as the candidates for follow-up experimental analyses. Data description Rhizoctonia solani AG-3 strain XEMS25-1 was isolated from disease leaves of tobacco target spot in Enshi, Hubei Province, China. The DNA was sequenced using Pacific Biosciences Sequel II (PacBio) and Illumina NovaSeq PE150 (Nova). Data from both sequencing platforms were combined, and the de novo assembly yielded an estimated 39.4 Mb genome. Completeness of the genome examined using Benchmarking Universal SingleCopy Orthologs (BUSCO) showed that the assembly had 93.7% of the 758 genes in fungi_odb10. PHI (Pathogen Host Interactions) database analysis revealed 519 reduced virulence genes, 91 loss of pathogenicity genes, 28 hypervirulence genes and 18 effectors might be the pathogenicity-related genes in R. solani AG-3 strain XEMS25-1. These genes could be selected as the RNA-silencing targets for exploring the molecular mechanisms of R. solani AG-3 pathogenicity on tobacco.